O potrzebie wspierania rozwoju kompetencji międzykulturowych i medialnych w kształceniu nauczycieli – w poszukiwaniu rozwiązań - Smoter, Katarzyna (Kultura-Społeczeństwo-Edukacja, 2018)
Smoter Katarzyna, O potrzebie wspierania rozwoju kompetencji międzykulturowych i medialnych w kształceniu nauczycieli – w poszukiwaniu rozwiązań [On the need to support the development of intercultural and media competences in the education of teachers – in search of solutions]. Kultura – Społeczeństwo – Edukacja nr 2(14) 2018, Poznań 2018, pp. 99–109, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2018.14.8. Today, a characteristic feature of life is contact (direct or via media) with “otherness” and the “Other” – ethnically, religiously, nationally. The issue of the links between multiculturalism and the media is essential for education, but it does not seem to be sufficiently taken into account in the formal education of teachers. Therefore, the article addressed the issue of shaping media competences and intercultural competences of teachers, indicating the need to include both these issues in an integral manner. It has become important to consider the dimensions of these competences – cognitive, pragmatic and emotional – as well as to show the issues that should be present in the education of teaching staff. This type of approach seems to meet the requirements relating to the dynamically forming “knowledge-based society and “multicultural society”.